2012
DOI: 10.1128/aem.01946-12
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Electron Transfer via Hydrogen and Formate Rather than Direct Electrical Connections in Cocultures of Pelobacter carbinolicus and Geobacter sulfurreducens

Abstract: Direct interspecies electron transfer (DIET) is an alternative to interspecies H 2 /formate transfer as a mechanism for microbial species to cooperatively exchange electrons during syntrophic metabolism. To understand what specific properties contribute to DIET, studies were conducted with Pelobacter carbinolicus, a close relative of Geobacter metallireducens, which is capable of DIET. P. carbinolicus grew in coculture with Geobacter sulfurreducens with ethanol as the electron donor and fumarate as the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 42 publications
6
138
0
1
Order By: Relevance
“…16,17 The gene for PilA, the structural protein for electrically conductive pili, was highly expressed (Fig. 2, Table S3 †), as expected 12,15 if the abundant Geobacter species were metabolizing ethanol with direct electron transfer to Methanosaeta.…”
Section: Evidence For Direct Electron Transfer In Digester Aggregatesmentioning
confidence: 87%
See 2 more Smart Citations
“…16,17 The gene for PilA, the structural protein for electrically conductive pili, was highly expressed (Fig. 2, Table S3 †), as expected 12,15 if the abundant Geobacter species were metabolizing ethanol with direct electron transfer to Methanosaeta.…”
Section: Evidence For Direct Electron Transfer In Digester Aggregatesmentioning
confidence: 87%
“…Studies with a diversity of mutant strains, decient in key aspects of interspecies H 2 /formate transfer or DIET, as well as genome-wide transcriptomic analysis, demonstrated that H 2 or formate could not be the interspecies electron carrier. 11,12,15 Instead, the co-cultures established electrical connections through the pili of the two Geobacter species, which are electrically conductive.…”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation
“…For energy-conserving electron disposal, Atribacteria expresses an electron-bifurcating formate dehydrogenase (Wang et al, 2013) and Fd red -dependent energy-conserving membranebound hydrogenase (Figures 2 and 3), suggesting that both formate and H 2 generation may take part in propionate degradation as observed in Syntrophobacter (Harmsen et al, 1998). Moreover, we identify that electron-bifurcating formate dehydrogenase is also encoded by Pelobacter carbinolicus (Pcar_1846-1843), a syntroph dependent on formate transfer (Dubourguier et al, 1986;Rotaru et al, 2012). Although propionate metabolism can be used in the reverse direction fermentatively, we did not detect any pathways for catabolizing fermentative substrates.…”
Section: Hdrabc (Supplementarymentioning
confidence: 88%
“…Summers et al [8] first reported DIET in co-cultures of Geobacter metallireducens and Geobacter sulfurreducens. They observed that DIET can be realized between different species through biological electrical connections by using the multiheme c-type cytochrome OmcS and electrically conductive pili [9]. Subsequently, Kato et al [10] suggested that cell-to-cell electron transfer can also be mediated through nonbiological conductive materials.…”
Section: Introductionmentioning
confidence: 99%